Cronossequência em sistema agroflorestal: impacto nos teores de carbono, água e nutrientes do solo - Morais, Adão Barros de (2022)
The agroforestry systems (AFS) has shown feasibility to restore soil fertility while combining production and conservation of natural resources, especially soil carbon. Therefore, the objective of this study was to evaluate the fertility level of the topsoil layer (0-10-cm) in an initial chronosequence of agroforestry systems (AFS) and to compare the results with two other land uses: native vegetation (VN), ecosystem reference of the coastal tableland forest, and bean crop in a monoculture system (MONO). The study was conducted in the Pachamama community, located in the municipality of Cascavel, Ceará. For this purpose, disturbed soil samples were collected in three soil use systems in five replications from two layers (0-5 cm and 5-10 cm), , allowing the following analyses: i) partitioned carbon; ii) phosphorus; iii) soil temperature and soil moisture; iv) soil bases content; and v) soil acidity. The evaluated partitioned carbon variables included the total organic carbon content (TOC) and its fractions, particulate organic carbon (COp) and organic carbon associated with minerals (COam). Phosphorus (P) and the soil bases potassium (K), calcium (Ca), magnesium (Mg) and sodium (Na) were measured as well. The AFS land use was split in a chronosequence of five different treatments, from zero (AFS0) to four years of implantation (ASF4). The means of the analysed variables were submitted to the normality test, subsequently to one-way analysis of variance (ANOVA), and compared by the Scott-Knott test at 5% of significance level. Soil management in the AFS chronosequence increased TOC levels by up to 322% in AFS2, 535% in AFS3 and 674% in AFS4 when compared to VN. The COp content of AFS2 was 70% higher than that of VN, while in AFS3 and AFS4 the COp content was equivalent to the values observed in VN. AFS2, AFS3 and AFS4 increased the COam content by at least twice and at most ninefold the VN content; the largest P content was observed in AFS1 and AFS2; base content and saturation (V%) were higher in AFS2 and AFS1, while and the maximum soil cation exchange capacity (CEC) was observed in AFS4; AFS3 and AFS4 developed moderate acidity; soil temperature in AFS and VN was up to 10°C lower than that recorded in MONO, while soil moisture in AFS4 and AFS3 was up to 50% higher than the values observed in the other soil uses. The results of this study allow to conclude that the AFS increased the TOC content, especially the most humified and stable fraction, COam; reduced P loss in AFS1 and AFS2; increased the CEC of AFS3 and AFS4; and the soil bases content was not directly related to the management. AFS increased the soil water content, possibly due to the high SOM content and subsurface water redistribution by the roots of heterogeneous functional groups of plants; and soil thermal balance was promoted due to sunlight interception by the canopy and soil cover.